Актуальні питання економічної освіти: підготовка бухгалтера-практика у ЗВО - Голуб, Наталя Олександрівна; Holub, Natalia (Запоріжжя : ТДАТУ, 2025)
UA: У статті розглянуто основні питання економічної освіти, а саме бухгалтера. Проаналізовано дослідження науковців щодо підготовки бухгалтера-практика у закладах вищої освіти. Визначено проблеми та перспективи впровадження. /// EN: The article considers the main issues of economic education, namely accounting. The research of scientists on the training of accountants practitioners in higher educational institutions is analyzed. Problems and prospects for implementation are identified.
Current issues of economic education: training of accountants’ practices in higher education institutions
Keywords: підготовка; бухгалтер; навчання; освітні курси; практичні навички; ринок праці; знання; training; accountant; training; educational courses; practical skills; labor market; knowledge